The Effect of the Science, Technology, Engineering, and Mathematics (STEM)-Based Problem-Based Learning (PBL) Model on Students’ Creative Thinking Skills in the Topic of Heat in Grade XI at SMAN 1 Ngadiluwih - Sastri, Putri Widya; Sari, Ambar (Impulse: Journal of Research and Innovation in Physics Education, 2025)
Students are often trained to find a single correct answer rather than to develop various possible solutions to a problem. This study employed a quantitative approach with a Quasi-Experimental design, specifically the Posttest-Only Control Group Design. Data were collected through observation sheets, tests, and documentation. The data analysis techniques used consisted of Instrument Testing, Prerequisite Testing, and Hypothesis Testing. Based on the results of the study, it can be concluded that: 1) There is an effect of the Science, Technology, Engineering, and Mathematics (STEM)-based Problem-Based Learning (PBL) model on students’ creative thinking skills, as indicated by the Mann-Whitney U test result with a significance value of 0.000 < 0.05. 2) The implementation of the STEM-based Problem-Based Learning (PBL) model effectively enhances students’ creative thinking skills on the topic of heat. The results of learning in each aspect of creative thinking show that the application of this model can serve as an alternative solution to create active, meaningful, and challenging physics learning.